Ryzyko i hedging z perspektywy producenta miedzi rafinowanej - Szeląg, Tomasz (Risk and Hedging from the Perspective of Refined Copper Producer, 2006)
Every kind of economic activity is associated with a risk. Making any simple decision is a risky task. It applies also to the refined copper producers, which face mainly copper price risk and currency risk. Until the mid-20th century, copper prices were settled by governments of countries that produced copper, regardless of stock quotations and situation in the world economy. In 1953, due to the huge increase of copper demand, both producer prices and stock ones rose simultaneously. Since then, copper prices have been driven by market factors and are very volatile, particularly during the last 15 years. In July 1944, during the UN Conference in Bretton Woods the new currency rules were established. Exchange rates were settled to the gold or US dollar. Many countries criticized this solution. Therefore, in August 1971 it was abolished and floating exchange rates were introduced two years later. Due to the volatility of copper prices and exchange rates, copper producers are forced to manage the market risks actively. It manifests itself not only in the usage of natural hedging but also in the usage of derivatives. The article reviews and presents academic papers in reference to the risk and hedging subjects. An effort was also made to confront a theory with the real economic processes, that exist on the copper market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (12); 2006; nr 1122, s. 56-73